First Feminist of Sub-Continent Molvi Mumtaz Ali’s Writing: “Haqooq e Niswaan” - Khan, Antars Arshad; Bhatti, Muhammad Rafique; Fatima, Riffat (sourcecoder, 2023)
First Feminist of Sub-Continent Molvi Mumtaz Ali’s Writing: “Haqooq e Niswaan” Shamsul Ulma Molvi Syyed Mumtaz Ali was a renowned expert of Persian and Arabic language. He was a very good translator of English and was a great scholar of Urdu. Molvi Mumtaz Ali was one of Sir Sayyad’s best companions as he dully fulfilled his part of reformation of Muslim society in his own way. In this article his book Haqooq_e Niswaan (1898) will be discussed. He narrates in the preface that he has distributed contents of this book into five parts: first one is based on the reasons (logical and assumed) of importance of men in Muslim society. Second part is about educating Muslim women. Third part refers to veil of women. Forth will deal with the matrimonial affairs and in the fifth part Molvi Mumtaz Ali discusses health and happiness of married life. For proving these points Molvi Mumtaz Ali turns himself into an expert religious scholar. He proves all his points’ logic first and then compares them with Quranic verses, Rawayah, and Hadith. We can call this book as the foremost revolution in women rights of Subcontinent.